The Role of Financial Inclusion and Women's Participation in Enhancing Food Sovereignty: Evidence from Coastal Communities - Wahyuni, Nurul; Prabowo, Rahmat Eko; Sharon, St Salmah; Arif, Muh; S, Sumarni (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the role of digital financial inclusion and women's participation in strengthening food independence among coastal communities in South Sulawesi. The research sample consisted of 100 female respondents from Takalar, Bantaeng, and Bulukumba Regencies. Data were collected using a structured questionnaire and analyzed through the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach. The findings reveal that digital financial inclusion has a positive but not significant effect on food independence (β=0.176; p=0.139), while women's participation has a positive and significant effect on food independence (β=0.568; p<0.001). Simultaneously, the two variables explain 50.4% of the variation in food independence, with the remaining 49.6% influenced by factors outside the model. These results highlight that the active role of women in economic activities, social participation, and household decision-making is more decisive in achieving food independence than mere access to digital financial services. The practical implication of this study emphasizes the importance of strengthening women’s empowerment programs through financial literacy and digitalization, as well as expanding cross-sector collaboration to support the achievement of the Sustainable Development Goals (SDGs), particularly in the areas of gender equality, poverty alleviation, and food security in coastal regions.